Biomass Feedstocks for Liquid Biofuels Production in Hawaii & Tropical Islands: A Review - Usman, Muhammad; Cheng, Shuo; Cross, Jeffrey Scott (International Journal of Renewable Energy Development, 2022)
Many tropical islands, including Aruba, Seychelles, Mauritius, and Pacific Island countries, are entirely dependent on importing fossil fuels to meet their energy demands. Due to global warming, improving energy use efficiency and developing regionally available renewable energy resources are necessary to reduce carbon emissions. This review analyzed and identified biomass feedstocks to produce liquid biofuels targeting tropical islands, particularly focusing on Hawaii as a case study. Transportation and energy generation sectors consume 25.5% and 11.6%, respectively, of Hawaii's imported fossil fuels. Various nonedible feedstocks with information on their availability, production, and average yields of oils, fiber, sugars, and lipid content for liquid biofuels production are identified to add value to the total energy mix. The available biomass conversion technologies and production costs are summarized. In addition, a section on potentially using sewage sludge to produce biodiesel is also included. Based on a comparative analysis of kamani, croton, pongamia, jatropha, energycane, Leucaena hybrid, gliricidia, and eucalyptus feedstock resources, this study proposes that Hawaii and other similar tropical regions can potentially benefit from growing and producing economical liquid biofuels locally, especially for the transportation and electricity generation sectors